Remote controlled curtain opener and closer / Aimy Nurliyana Md Yusof & Mohamad Nur Farid Kamarozaman - Md Yusof, Aimy Nurliyana; Kamarozaman, Mohamad Nur Farid (2015)
First of all, this report is to state clearly about the project made which are the remote controlled curtain opener and closer. This project is made in order to fulfil the objectives that been made which are to identify function of motor, the role of every component used in the circuit in this project and analyze the connectivity of the remote used with the circuit. Significantly, this project able to create a simple close loop system of opening and closing a curtain which driven by electrical motor used. The main component of this project is the DC Low Speed Motor, RF transmitter and RF receiver. These three components will be connected as the RF transmitter will gives the input signal from the user and the RF receiver which linked together with the DC Low Speed Motor will get the signal either to open or close the curtain. Besides, the Arduino is used to indicate the opening and the closing the curtain by controlling the lighting pattern of the LEDs used. The control circuit is connected directly with the power supply and the remote will use the suitable battery so that the design of the remote is flexible enough for user to use the curtain opener and closer. Therefore, this project able to ease people with improved technology that the usual design besides a new technology is developed to build a smart home.